Structure evolution in tribological interfaces studied by multilayer model alloys - Cihan, Ebru (KIT Scientific Publishing, 2020)
Recent studies of deformation mechanisms of metals and alloys pioneer the better investigation of the friction and wear behavior of materials with well-defined initial microstructures. Within this scope, in this work, the effect of sub-surface deformations on the resulting friction and wear behavior has been searched by means of a systematic experimental study on Au-Ni metallic multilayer model alloy system.